Long‐term prognosis of human herpesvirus 6 reactivation following allogeneic hematopoietic stem cell transplantation. Issue 6 (19th June 2018) - Iesato, Kotoe; Hori, Tsukasa; Yoto, Yuko; Yamamoto, Masaki; Inazawa, Natsuko; Kamo, Kenichi; Ikeda, Hiroshi; Iyama, Satoshi; Hatakeyama, Naoki; Iguchi, Akihiro; Sugita, Junichi; Kobayashi, Ryoji; et al.
Abstract: Background: Patients undergoing hematopoietic stem cell transplantation (HSCT) frequently have HHV‐6 reactivation typically during the early phase following HSCT. The long‐term clinical complications and prognosis, however, remain unclear. Methods: Between September 2010 and October 2012, whole blood samples from 105 patients collected weekly from prior to 6 weeks after HSCT underwent multiplex polymerase chain reaction (PCR) to screen for viral DNA, followed by real‐time PCR for quantitative estimation. In 48 patients, only HHV‐6 was detected in at least one sample. In 30 patients, no viral DNA was detected. Long‐term clinical records were reviewed in March 2016. All 48 HHV‐6‐positive patients, and 24 patients in whom no viral DNA detected, were followed up. Results: Median maximum HHV‐6 DNA load in the blood of the HHV‐6 reactivation group ( n = 48) was 11 800 copies/μg peripheral blood leukocyte DNA (range, 52–310 000 000). Hemophagocytic syndrome (HPS) was diagnosed in two subjects with HHV‐6 reactivation. Acute graft‐versus‐host disease (GVHD) developed more frequently in patients with HHV‐6 reactivation than in patients without viral reactivation ( P = 0.002), but there was no difference in incidence of chronic GVHD. There was no difference in engraftment of neutrophils and platelets between groups. There was also no difference in overall survival between groups. Onset of HPS, however, was associated with lower overall survival ( P = 0.009). Conclusions: Human herpesvirus 6 reactivation was associated with acute GVHD, but not with chronic GVHD, engraftment or overall survival. Onset of HPS, however, predicts lower overall survival.